(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Language psychology is a science that studies the psychological processes of a person related to language, a field that places a great emphasis on the mental activity of a person and the formation, development of speech and internal psychological mechanisms in its application. Language psychology analyzes how human consciousness affects language, psychological factors in language acquisition, as well as the processes of human interaction through speech. Language is not only a means of communication, but also a complex social phenomenon that is inextricably linked with the main psychological processes of a person, such as thinking, memory, attention, feelings.